Character Education on E-Books Through Literature Circles: Practices and Experiences - Sa'adah, Lailatus (IJEE (INDONESIAN JOURNAL OF ENGLISH EDUCATION), 2025)
Understanding and reflecting on character education is more than just knowledge; it is also awareness and action to carry out which can be done while being a teacher. A qualitative study was conducted to collect data from 27 pre-service teachers who participated in the Extensive Reading Course in order to understand how reading e-books and having discussions through Literature Circles have consequences for their character education. Several instruments, including recorded class discussions, questionnaires, and interviews, used to learn how Literature Circles in Extensive Reading classes can provide pre-service teachers with an entry point into conversations about character education, help pre-service teachers better understand themselves and their students, and serve as a first step in a learning environment. The findings of this study give pre-service teachers with an overview of how Literature Circles might provide critical implications for character education as a provision for establishing character education. Literature Circles are instructional activity that aspiring pre-service teachers can utilize to provide a safe environment to participate in conversations and to support pre-service teachers as they work on developing positive classroom character.